Analisis Perusahaan Asuransi Syariah Di Indonesia Periode 2019-2022 Dengan Metode DEA (Data Envelopment Analysis) - Luthfi Ajisantoso; Nadiyatul Aulia; Nasiatul Hana Fikriyah; Rani Meisya Fitriani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The growth of sharia insurance from 2019-2022 shows that sharia insurance is still developing in society. However, there will be a decline in 2022 in general insurance and reinsurance on investments and assets which have an important role in running a sharia insurance company. The aim of this research is to determine the level of efficiency of sharia insurance companies in Indonesia for the 2019-2022 period using the DEA method. This research was carried out using quantitative methods where the emphasis is more on data processing, proving hypotheses and using statistical tools to make it easier for researchers to manage data. The data used in this research is Time Series, namely data that has a time series of more than one year on one object or data collected over time on individuals or objects.